2020
DOI: 10.1007/s00344-020-10251-9
|View full text |Cite
|
Sign up to set email alerts
|

γ-Aminobutyric Acid Participates in the Adult-Phase Adventitious Rooting Recalcitrance

Abstract: In many tree species especially the rooting-recalcitrant woody perennials, the adventitious root (AR) in the juvenile phase can be easily induced by exogenous auxin, but AR formation becomes recalcitrant in the adult phase. Also, it is reported that the γ-aminobutyric acid (GABA) inhibits primary root growth in Arabidopsis and the AR formation in poplar (Populus ssp). So far, how GABA affects or is affected by the ontogenetic phase or auxin remains unclear. Here, we used an apple rootstock, Malus xiaojinensis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 61 publications
2
9
0
Order By: Relevance
“…GAD gene encodes glutamate decarboxylase, which can catalyze glutamate decarboxylate to form γ‐aminobutyric acid (GABA; Bown & Shelp, 1997). As shown in our previous study, GABA participates in the adult‐phase apple rootstock adventitious rooting recalcitrance (Li, Xu, et al., 2021). Previous studies found that significant increases in expression of GABA synthetic enzyme genes GAD , activity of GAD, and GABA concentration were detected in adult‐phase cuttings, but not in juvenile‐phase cuttings in apple rootstock (Li, Xu, et al., 2021).…”
Section: Resultssupporting
confidence: 57%
See 3 more Smart Citations
“…GAD gene encodes glutamate decarboxylase, which can catalyze glutamate decarboxylate to form γ‐aminobutyric acid (GABA; Bown & Shelp, 1997). As shown in our previous study, GABA participates in the adult‐phase apple rootstock adventitious rooting recalcitrance (Li, Xu, et al., 2021). Previous studies found that significant increases in expression of GABA synthetic enzyme genes GAD , activity of GAD, and GABA concentration were detected in adult‐phase cuttings, but not in juvenile‐phase cuttings in apple rootstock (Li, Xu, et al., 2021).…”
Section: Resultssupporting
confidence: 57%
“…As shown in our previous study, GABA participates in the adult‐phase apple rootstock adventitious rooting recalcitrance (Li, Xu, et al., 2021). Previous studies found that significant increases in expression of GABA synthetic enzyme genes GAD , activity of GAD, and GABA concentration were detected in adult‐phase cuttings, but not in juvenile‐phase cuttings in apple rootstock (Li, Xu, et al., 2021). We found that the promoter region of GAD5a gene exhibited significantly high methylation levels in ‘T337’_R compared with ‘T337’_A in CHH content (Figure 7a).…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…In inbreeding plants, GEBV is estimated in many GS models such as rr-BLUP, Bayesian least absolute shrinkage and selection operator (LASSO) etc., which emphasizes additive effects [11] . In outbreeding species, however, non-additive effects contribute to a large proportion of the genetic variations due to the high level of heterozygosity and the clonal propagation of many outcrossing plants [2] , [72] . In the GAP models, the genetic effect includes both allelic additive and non-additive effects, the prediction accuracy was therefore higher than that obtained by rr-BLUP.…”
Section: Discussionmentioning
confidence: 99%